Pharmacological Interventions to Circadian Clocks and Their Molecular Bases. Issue 12 (29th May 2020) - Miller, Simon; Hirota, Tsuyoshi
Abstract: Daily physiological rhythms are regulated by the body's internal timekeeper known as the circadian clock. Expression, post-translational modification, and degradation of clock proteins constituting the circadian clock are precisely controlled in a rhythmic manner. Perturbation of these processes by nature and nurture results in physiological dysfunction and diseases. Small-molecule modulators of clock or clock-related proteins can adjust clock functions, and thus represent a promising method of therapeutic treatment for a range of clock-related diseases. In this review, we will introduce the identification and development of small-molecule compounds that target clock proteins, as well as X-ray crystal structures of protein-compound complexes that facilitate the understanding of clock protein regulation and drug derivatization. Furthermore, we describe the effects of these compounds in a diseased setting and discuss the therapeutic potential of clock modulators. Graphical abstract: Image 1 Highlights: Clock proteins are regulated posttranslationally by protein kinases. Target-based and phenotypic screening identified clock-modulating compounds. Clock-modulating compounds regulate protein kinases and clock proteins. Crystallographic studies facilitate understanding of clock-modulating compounds. Clock-modulating compounds have therapeutic potential in a host of diseases.